Social issues in the considerations of classical economists - Danowska-Prokop, Barbara (Kwestie społeczne w rozważaniach klasyków ekonomii, 2019)
For many years, social security was motivating not only individuals but also researchers to act, however a new approach to the problem was associated with the rise of capitalist reality, i.e. the processes of the economy and society’s modernisation. The process of modernisation was closely related to transformations in two spheres: economic, i.e. three revolutions: agrarian, commercial and industrial, and social, i.e. the formation of an industrial society and the ongoing process of democratisation of social life. Capitalist reality forced a new approach not only to the management process but the position of Man in this process (the new reality revealed deficiencies in the existing system of values and thus in the perception of personal and interpersonal relations). While exalting humanity and its needs, the new social and economic reality has forced a different view of social issues and thus the role of the state in the simultaneously occurring process of growing wealth and the impoverishment of society. This left its mark in the approach of classical economists and their successors to social issues
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 25-34
Keywords: classical economics; social issues; market; state; ekonomia klasyczna; kwestie społeczne; rynek; państwo